Joint effect of modifiable risk factors on Parkinson’s disease: a large-scale longitudinal study - Li, Panlong; Zhu, Xirui; Liu, Min; Wang, Yanfeng; Huang, Chun; Sun, Junwei; Tian, Shan; Li, Yuna; Qiao, Yuan; Yang, Junting; Cao, Shanshan; Cong, Chaohua; et al. (Frontiers in Human Neuroscience, 2025)
IntroductionPrevious researches have often underestimated the diversity and combined effects of risk factors for Parkinson’s disease (PD). This study aimed to identify how multiple modifiable risk factors collectively impact PD.MethodsThe study included 452,492 participants from the UK Biobank, utilizing genetic data and 255 phenotypic variables. A broad exposure association study was conducted across seven domains: socioeconomic status, medical history, psychosocial factors, physical measures, early life, local environment, and lifestyle. Risk scores of each domain for each participant were generated. The joint effects of modifiable and genetic risks assessed using Cox proportional hazards model. Population attributable fraction (PAF) was estimated to quantify contribution ratio of risk factors in different domains to the occurrence of PD.ResultsMultiple risk factors significantly (p < 1.96 × 10−4) associated with PD was observed. The top 5 factors were hand grip strength (hazard ratio (HR) = 0.98, p = 1.59 × 10−24), long-standing illness (HR = 1.38, p = 3.63 × 10−20), self-reported nervousness (HR = 1.56, p = 5.9 × 10−20), ever suffered from mental health concerns (HR = 1.42, p = 5.48 × 10−18) and chest pain (HR = 1.42, p = 1.43 × 10−18). Individuals with unfavorable medical history, psychosocial factors, physical measures, and lifestyle had an increased risk of PD by 33 to 51% compared to those with favorable factors (p < 0.001).DiscussionResults indicated that addressing modifiable risk factors, especially in physical measures and psychological factors, could potentially prevent up to 33.87% of PD cases. In formulating prevention strategies, it is recommended to prioritize domains such as physical measures, psychosocial factors, lifestyle, and medical history.